Ionic liquid‐modified graphene/poly(vinyl alcohol) composite with enhanced properties. Issue 26 (1st March 2017) - Wang, Lei; Wang, Wenwen; Fan, Ping; Zhou, Menglong; Yang, Jintao; Chen, Feng; Zhong, Mingqiang
ABSTRACT: How to preserve the structure integrity of graphene while enhance its dispersion and compatibility in matrix attracts the attention of researchers in graphene/polymer nanocomposite field. In this paper, methacryloxyethyltrimethyl ammonium chloride (DMC), a kind of ionic liquids, was first used to non‐covalently functionalize graphene in the process of graphene oxide (GO) reduction. The as‐modified graphene (DMC‐rGO) was further incorporated into poly(vinyl alcohol) (PVA) matrix by solution casting technique to fabricate DMC‐rGO/PVA composites. The structure and properties of the obtained DMC‐rGO were investigated by X‐ray diffraction analysis (XRD), X‐ray Photoelectron Spectroscopy (XPS), Transmission Electron Microscope (TEM), Atomic force microscopy (AFM), and Raman test. The results showed that graphene could be successfully modified by DMC through ionic–π interaction and the structure integrity of the graphene could be reserved by this non‐covalently approach. Furthermore, after co‐reduction process, some hydroxyl groups were introduced into DMC‐rGO. In virtue of these intrinsic properties of DMC‐rGO, the fabricated DMC‐rGO/PVA composites exhibit considerable enhancements in mechanical properties and remarkable improvements in thermal stability, as well as the enhancement in electrical conductivity at low DMC‐rGO loading. This simple modification approach gives a new opportunity to improve the performances of graphene/polymer composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45006. Abstract :